Biphasic Effect of Diabetes on Neuronal Nitric Oxide Release in Rat Mesenteric Arteries - Sastre, Esther; Caracuel, Laura; Blanco-Rivero, Javier; Callejo, María; Xavier, Fabiano E.; Balfagón, Gloria (PLOS ONE, 2016)
Introduction We analysed possible time-dependent changes in nitrergic perivascular innervation function from diabetic rats and mechanisms implicated. Materials and Methods In endothelium-denuded mesenteric arteries from control and four- (4W) and eight-week (8W) streptozotocin-induced diabetic rats the vasoconstriction to EFS (electrical field stimulation) was analysed before and after preincubation with L-NAME. Neuronal NO release was analysed in the absence and presence of L-arginine, tetrahydrobiopterine (BH4) and L-arginine plus BH4. Superoxide anion (O2-), peroxynitrite (ONOO-) and superoxide dismutase (SOD) activity were measured. Expressions of Cu-Zn SOD, nNOS, p-nNOS Ser1417, p-nNOS Ser847, and Arginase (Arg) I and II were analysed. Results EFS response was enhanced at 4W, and to a lesser extent at 8W. L-NAME increased EFS response in control rats and at 8W, but not at 4W. NO release was decreased at 4W and restored at 8W. L-arginine or BH4 increased NO release at 4W, but not 8W. SOD activity and O2- generation were increased at both 4W and 8W. ONOO- decreased at 4W while increased at 8W. Cu-Zn SOD, nNOS and p-NOS Ser1417 expressions remained unmodified at 4W and 8W, whereas p-nNOS Ser847 was increased at 4W. ArgI was overexpressed at 4W, remaining unmodified at 8W. ArgII expression was similar in all groups. Conclusions Our results show a time-dependent effect of diabetes on neuronal NO release. At 4W, diabetes induced increased O2- generation, nNOS uncoupling and overexpression of ArgI and p-nNOS Ser847, resulting in decreased NO release. At 8W, NO release was restored, involving normalisation of ArgI and p-nNOS Ser847 expressions.